Analisis Produktivitas Jagung di Kecamatan Pulubala, Kabupaten Gorontalo - Abdullah, Arlan; Olilingo, Fahrudin Zain; Akib, Fitri Hadi Yulia (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the influence of production factors, including seeds, fertilizer, land area, labor, pesticides, and capital, on corn productivity in Pulubala District, Gorontalo Regency. The research employs a quantitative approach, with primary data collected through questionnaires, interviews, and observations of 100 respondents. Data analysis was conducted using multiple linear regression with SPSS, complemented by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that, simultaneously, all independent variables significantly affect corn productivity. Partially, seeds, fertilizer, labor, and capital have a positive and significant effect, whereas land area and pesticides have a negative and significant effect. The coefficient of determination (R²) of 0.705 indicates that 70.5% of the variation in corn productivity can be explained by the independent variables in the model, while the remaining 29.5% is influenced by other factors outside the study. Descriptive analysis also shows that the average corn productivity in Pulubala District reaches 5.085 tons per hectare